Effect of three drying methods on the drying characteristics and quality of okra. Issue 8 (10th June 2016) - Huang, Jiapeng; Zhang, Min
ABSTRACT: The objective of this study was to compare the drying characteristics and quality of dried okra obtained by vacuum freeze drying (VFD), microwave vacuum drying (MVD), and pulse-spouted microwave vacuum drying (PSMVD). The quality parameters include color ( L*, a*, and b* ), texture (hardness and fracturability), shrinkage ratio (SR), nutrient retention (chlorophyll, flavonoids, and vitamin C), and sensory score was investigated. Vacuum freeze drying maximally preserved the original properties of samples. And the samples dried by PSMVD showed higher quality and more uniformity compared to MVD. Considering of all aspects comprehensively, such as cost-effectiveness, practicability, and scale-up, PSMVD was a promising technique which would match results obtained by vacuum freeze drying.